Research on applicability of containment test data for HPR1000 based on phenomena scaling - Liu Yusheng; Qiao Xuedong; Tan Sichao; Jing Jianping; Wang Ting; Zhu Yuanbing (International Journal of Advanced Nuclear Reactor Design and Technology, 2025)
The volume of the nuclear power plant containment is huge, making it difficult to conduct equal-scale or large-scale thermal-hydraulic tests. Currently the test data mainly come from small-scale tests. To address the applicability of small-scale containment test data in validation process of the containment performance analysis code, the analysis method for applicability of experimental data is proposed and developed on the basis of similarity analysis of the pressure response process in the containment. The applicability study of the test data, which are produced by some scaled containment facilities such as the HDR, Battelle and CVTR, is carried out in combination with the test parameters. The applicability of each test case isobtained respectively when they are applied to validate the containment code in case of the Large Break Loss of Coolant Accident (LBLOCA) and Main Steam Line Break Accident (MSLB) of HPR1000 nuclear power plant. The results show that the similarity criteria for pressure response process and key phenomena within the containment vessel under accident conditions can be employed to analyze the applicability of different containment tests to specified power plant. The test dataoriginating fromHDR ISP-16 and HDR ISP-23can represent the pressure transient process, results of coupling phenomena such as mass and energy release at the break, condensation near the containment shell and internals, within the HPR1000 containment in case of LBLOCA or MSLB. The distortion is either within the acceptable range or conservative for design limits of containment pressure, so that the small-scale containment test data could be suitable for verification and validation of the HPR1000 containment thermal hydraulic response analysis code.